Investigating the role of accepting learning management system on students' engagement and sense of community in blended learning - Üstün, Ahmet Berk; Karaoğlan Yılmaz, Fatma Gizem; Yılmaz, Ramazan; Yılmaz, Ramazan; Karaoğlan Yılmaz, Fatma Gizem; Üstün, Ahmet Berk (Springer, 2021)
The purpose of this study was to investigate the structural relationships between university students' acceptance of a learning management system (LMS), sense of community and engagement in a blended learning (BL) environment. This study was conducted in an introductory computer course with students who participated in a Moodle learning community that was constituted for the BL course. Three self-report instruments were employed to gather data from 168 university students studying at a public university. The path analysis with structural equation modeling (SEM) confirmed that students' LMS acceptance was related to their sense of community and engagement in BL. The findings revealed that students' LMS acceptance significantly and positively affected their sense of community and engagement in BL. Moreover, perceived usefulness and perceived ease of use of LMS were uncovered as influential factors in increasing their sense of community and engagement. The findings of the study imply that instructors should ensure students' acceptance of LMS to establish learning communities in which they have opportunities for collaborative, interactive and engaging learning activities in the delivery of BL.
Keywords: Learning Management System Acceptance; Sense Of Community; Engagement; Blended Learning; Structural Equation Modeling